2013
DOI: 10.1080/17482798.2012.739756
|View full text |Cite
|
Sign up to set email alerts
|

What Makes a Bully a Cyberbully? Unravelling the Characteristics of Cyberbullies across Twenty-Five European Countries

Abstract: The characteristics of bullies who act face to face and those who do so in cyberspace were compared directly in one sample across 25 countries. The nature of cross-country differences due to their technological infrastructure was also explored. Cyberbullies compared to face-to-face bullies were more likely to engage in risky online activities, spend more time online, and were finding it easier to be themselves online. Private access to the internet did not make a difference. Gender differences showed girls mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
51
1
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 99 publications
(60 citation statements)
references
References 49 publications
5
51
1
3
Order By: Relevance
“…To date, most research has focused on describing the current situation with regard to cyberbullying, addressing such aspects as the prevalence of cyberbullying (Riebel, Jäger, & Fischer, 2009), the profiles of bullies (Görzig & Ó lafsson, 2012) and victims (Katzer, Fetchenhauer, & Belschak, 2009), and the impact of cyberbullying (Bonanno & Hymel, 2013) in addition to related definitional and measurement issues (Menesini & Nocentini, 2009). Most of these situation analysis studies are based on surveys among young people.…”
Section: Literature Reviewmentioning
confidence: 99%
“…To date, most research has focused on describing the current situation with regard to cyberbullying, addressing such aspects as the prevalence of cyberbullying (Riebel, Jäger, & Fischer, 2009), the profiles of bullies (Görzig & Ó lafsson, 2012) and victims (Katzer, Fetchenhauer, & Belschak, 2009), and the impact of cyberbullying (Bonanno & Hymel, 2013) in addition to related definitional and measurement issues (Menesini & Nocentini, 2009). Most of these situation analysis studies are based on surveys among young people.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The study found that online aggression was typically distinct from traditional bullying as there was more reciprocal, back and forth interactions where the same individual would often be both victim and aggressor. Finally, bullying rates have traditionally been higher in males than females; however, online gender differences do not play as large of a role (Görzig and Ólafsson ; Navarro and Jasinski ).…”
Section: The Problems Defining Cyberbullyingmentioning
confidence: 99%
“…Sociale netwerksites, zoals Facebook, zijn binnen korte tijd enorm populair geworden (Lenhart e.a., 2010), en adolescenten zijn experts op het gebied van online communiceren (Valkenburg & Peter, 2011). Jongeren gaan echter ook vaak lichtzinnig te werk bij het produceren en gebruiken van online informatie (Deursen, Van Dijk & Peeters, 2011;Fogel & Nehmad, 2009;Walraven, Brand-Gruwel & Boshuizen, 2009), hetgeen kan leiden tot negatieve online ervaringen (Görzig & Ólafsson, 2013;Peter & Valkenburg, 2006). Vergelijkend onderzoek naar specifiek online risicogedrag is schaars.…”
Section: Inleidingunclassified